IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK DI RSUD RAA SOEWONDO PATI - Ernawati, Aeda (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2016)
ENGLISHLocal Regulation of Pati District No. 10 of 2014 states that the hospital is one of the smoke free areas. The purpose of this study was to describe the implementation of smoke-free area policy in RAA Soewondo Hospital, Pati District, focusing on program, implementation and targeted groups. This study used a qulitative approach that was conducted on February to August 2016. The number of informants was 12, consists of 2responsible employees for smoke-free-area implementation, 5 hospital employees, and 5 visitors. The data were collected through interview as well as observation and analyzed descriptively. The results showed that the implementation of smoke-free area policy has not been optimized yet. Specific department that is responsible for policy implementation was not existed. Socialization and monitoring have been conducted although they were not optimal. The hospital has not had a guideline for punishment. The organization has not allocated specific budget for policy implementation. The participaton of targeted group was low. The organization might improve the participation of targeted groups by increasing the awareness regarding collective responsibility on the implementation of smoke-free area in the hospital. Moreover, the local government should accelerate the legalization of the guideline of free-smoke area policy.Â INDONESIARumah sakit merupakan salah satu kawasan tanpa rokok berdasarkan Peraturan Daerah Kabupaten Pati No 10 Tahun 2014. Tujuan penelitian untuk menggambarkan implementasi Peraturan Daerah Kabupaten Pati No 10 Tahun 2014 di RSUD RAA Soewondo Pati berdasarkan unsur pelaksana, program dan kelompok sasaran. Penelitian menggunakan pendekatan kualitatif dilaksanakan pada bulan Pebruari sampai Agustus 2016. Informan berjumlah 12 orang terdiri 2 orang pegawai pelaksana kebijakan KTR, 5 orang karyawan dan 5 pengunjung. Pengumpulan data dengan wawancara dan observasi. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan kebijakan KTR di RSUD RAA Soewondo Pati sudah dilaksanakan, tetapi belum optimal. Belum ada bagian yang bertanggungjawab secara khusus terkait pelaksanaan kebijakan KTR. Program KTR berupa sosialisasi dan pengawasan sudah dilaksanakan tetapi belum efektif. Pemberian sanksi sulit dilaksanakan karena belum ada pedomannya. Belum ada anggaran khusus untuk program KTR. Peran serta kelompok sasaran masih rendah. Untuk itu perlu peningkatan partisipasi kelompok sasaran dengan meningkatkan pemahaman tentang tanggung jawab bersama dalam mewujudkan KTR di lingkungan rumah sakit. Peraturan Bupati tentang Pedoman Pelaksanaan KTR di Kabupaten Pati perlu segera disahkan.